Mediational component for didactic mathematical knowledge of Statistics in pre service teachers: an exploratory assessment study - Pedro Arteaga; Carmen Batanero; María Magdalena Gea (Educação Matemática Debate, 2017)
We analyse the meditational component of didactic mathematical knowledge related to elementary statistics in a sample of 108 pre service primary school teachers when analysing the med iational suitability of a statistical project. Using the guide to analyse the didactic suitability proposed by Godino (2013) we study the levels in the different descriptors and components of mediational suitability. Our results suggest the need to reinfor ce the mediational component of teacher’ knowledge about statistics.